UV-curable interpenetrating polymer networks based on acrylate/vinylether functionalized urethane oligomers - ÇAKIR, MUSTAFA; KAYAMAN APOHAN, NİLHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The synthesis of simultaneous full interpenetrating polymer networks (IPN) based on Bisphenol A or 6F Bisphenol A bearing acrylated urethane (Bis A or 6F Bis A based Acryl-U) oligomers and vinylether functionalized polydimethyl siloxane containing urethane oligomer (PDMS-VEU) is described. The structures of the oligomers were characterized by FTIR. All resins were successfully polymerized by UV-irradiation in the presence of corresponding reactive diluents and photoinitiators. Physical properties of IPNs were determined by extraction and water absorption measurements. Extractable parts of IPNs were found to be approximately between 10 and 35 wt%. The stress-strain tests showed that an improvement was obtained on tensile properties by addition of PDMS-VEU oligomer to the Bis A based Acryl-U resin. In addition IPN sample (90/10 wt%) has higher thermo-oxidative stability compared to the neat films. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: UV-curing; interpenetrating polymer networks; vinylethers; 6F bisphenol A; poly(dimethyl siloxane); HYDROGEL NETWORKS; CURING BEHAVIOR; CURED EPOXY; MODEL VERS; SYSTEMS; METHACRYLATE)